Influence of halloysite nanotube on hydration products and mechanical properties of oil well cement slurries with nano-silica. (30th June 2020) - Liu, Huiting; Jin, Jianzhou; Yu, Yongjin; Liu, Huimin; Liu, Shuoqiong; Shen, Jiyun; Xia, Xiujian; Ji, Hongfei
Highlights: HNT was used to reinforce mechanical properties of oil well cement. Effects of HNT on hydration products of oil well cements were discussed. Cross-linking and more dense micro-structure could be observed in oil well cement with HNT HNT improved the pore structure and decreased the gas permeability of cement. Abstract: Excellent physical and chemical properties of halloysite nanotube make it potential to reinforce cement composites. In this study, effects of halloysite nanotube on mechanical properties of oil well cement were investigated. The results showed that the compressive and flexural strength of cement with 3% halloysite nanotube was increased by 40.8% and 49.2%, respectively and the elasticity modulus decreased by 20.01% after curing for 28 days, which demonstrated that halloysite nanotube cement had high strength and good toughness. TG-DTA, SEM, XRD, MIP tests were carried out to study the hydration products and microstructure changes in cement samples after adding halloysite nanotube. Optimized hydration products, lower permeability up to 38.82%, cross-linking and denser microstructure all contributed to excellent mechanical properties of oil well cement with halloysite nanotube.